Automated Malicious File Investigation - RAMA ROA, SHARVITA (IRC, 2020)
UCheck Sandbox is an application system where it can perform a task of verifying the authenthication of a file upload or an URL upload to combate cyber security. This report covers the studies made on the technologies that can be used to develop a reliable online safety precaution application for University Teknology PETRONAS (UTP). The main reason of this project is to come up with an application where they can run the suspicious files and links to check the if there is any malicious content in it before opening the links or attachments and anyone in the organisation can bravely open files and links online without the fear of their accounts will be hacked or compromised in any online system in UTP that can be used to minimize the malicious activities among hackers whom are trying to trespass UTP information illegally. Moreover, the main objectives of this project is to identify the awareness level of cyber security threats among UTP community and to develop a tool for combating cyber security threats by using a reliable application where it will send a result after checking the file or URL upload to ensure the authenticity of the file. At this moment, University Teknology PETRONAS (UTP) doesn’t have this system and such system is beneficial for all. This system will be developed by using waterfall methodology because waterfall methodology is the most suitable as the knowledge on required algorithms and techniques are described in this report. Moreover, survey has been done during requirement gathering phase and a system architecture has been designed. The development of the project has taken place where Cuckoo Sandbox has been integrated with Visual Studio Code, Firebase and Vultr into an application as well as testing has been done. Lastly, the maintenance of the project is currently been taken care as sometimes the server crashes and technical issues.